Ultrasonic features of the placenta, umbilical cord, and amnion in pregnant smokers - Gryzunova E.M; Baranov A.N; Soloviev A.G; Kazakevich E.V; Chumakova G.N; Kharkova O.A (LCC «Medicine-Inform», 2018)
Ultrasonic features of the placenta, umbilical cord, and amnion in pregnant smokers Gryzunova E.M.1, Baranov A.N.2, Soloviev A.G.2, Kazakevich E.V.1, ChumakovaG.N.2, Kiseleva L.G.2, Kharkova O.A.2 1 Northern Medical Clinical Center named after N.А. Semashko, Arkhangelsk 2 Northern State Medical University, Arkhangelsk Smoking is one of the risk factors for the development of violations in the fetoplacental system, and one of the most important preventable factors of adverse pregnancy outcomes for both mother and fetus. Aim: detection of ultrasound features of the placenta, umbilical cord, amnion in pregnant smokers to improve the diagnosis of the fetal condition under the influence of tobacco smoke components. Patients and Methods: a cohort for the survey was formed of 120 women with the use of the inclusion criteria. Group I included pregnant non-smokers (40 women), group II - pregnant smokers (80 women). Comparison of fetal development in the group of smokers was carried out in two subgroups: IIa - those who reported smoking only in the first trimester (embryonic period, 40 women) and IIb - those who reported smoking throughout the pregnancy (40 women). Results: pregnant smokers significantly more often revealed signs of placental insufficiency compared to non-smokers (p<;0,001). The thickness of the placenta in the group of pregnant smokers was significantly less (p<;0,034) in comparison with the group of nonsmokers. Placental calcification in pregnant smokers was two times higher compared with non-smokers (p<;0,002). The diameter of the umbilical cord in one-third of pregnant smokers was under the fifth percentile with an accuracy of p<;0,001 compared with non-smokers. The long-term effects of tobacco smoke products on the placenta lead to the progression of such signs of placental insufficiency as: placental calcification; placental insufficiency. Conclusion: quitting smoking favorably affects the decline in the rate of development of smoking-induced disorders, including the incidence and severity of placental insufficiency. Key words: pregnancy, fetus, placenta, umbilical cord, amniotic fluid, fetoplacental complex, tobacco smoking. For citation: Gryzunova E.M., Baranov A.N., Soloviev A.G. et al. Ultrasonic features of the placenta, umbilical cord, and amnion in pregnant smokers // RMJ. 2018. № 2(I). P. 23-26.